Effect of Rural-Urban Migration on Age at Marriage Among Adolescent Girls in Bangladesh - Antu, Jannatul Ferdous; Parvin, Kausar; Sujan, Hasan Mahmud; Mamun, Mahfuz Al; Naved, Ruchira Tabassum (Frontiers in Public Health, 2022)
Objectives: Bangladesh reports one of the highest rates of child marriage (CM) (59%) in the world and the highest rate within South Asia. Age at marriage of girls is a critical human rights and developmental issue in Bangladesh. Migration has been documented to be positively associated with age at marriage. Bangladesh experiences one of the highest rates of rural to urban migration in the world. An increase in rural-urban migration of adolescent girls has been observed over the last few decades in Bangladesh with the expansion of employment opportunities particularly in the ready-made garment industry (RMG). This analysis explores the effect of migration on age at marriage and CM among adolescent girls living in urban slums of Dhaka. Methods: The sample was selected from icddr,b’s Urban Health and Demographic Surveillance System (UHDSS) and comprises of never-married adolescent girls aged 15-19, who migrated in from rural Bangladesh to slums in and around Dhaka during 2015-2019. These in-migrants were matched with their rural counterparts from icddr,b’s Matlab HDSS (MHDSS), using one to one nearest neighbor matching with caliper 0.1 using propensity score matching (PSM) method. The sample derived included a total of 2700 never-married adolescent girls from Dhaka and Matlab. The association between migration and age at first marriage was estimated using a linear regression model and the effect of migration on CM was explored using logistic regression analyses. Results: The in-migrants perfectly matched with their rural peers in terms of age, household wealth and religion. However, their income earning status was hugely different. A higher proportion of in-migrant girls were never-married compared to the rural control group in December, 2019 in both 15-19-year (Coefficient, 1.77; 95% CI, 1.07-2.46) and 20-24-year age groups (Coefficient, 2.87; 95% CI, 2.18-3.55). The migrant girls aged 20-24 years were 71% (aOR, 0.29; 95% CI, 0.12-0.69) less likely to get married before CM age bar in Bangladesh compared to their rural counterparts. Conclusion: Migration has a positive effect on delaying marriage and reducing CM among adolescent girls. Findings from this study suggest that CM can be reduced by creating educational and economic opportunities for females.